A Semantic Analysis of the Root [س-ل-م] and Its Derivatives in the Qur'an: A Case Study of the Indonesian Ministry of Religious Affairs Qur'an Translation - Ramadhan, Rezky; Haeruddin, Haeruddin; Baso, Yusring Sanusi; Andi, Agussalim (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
In the Qur'an, changes in morphological patterns (wazan) not only produce grammatical variations, but also give birth to differences in meaning. One of the most productive roots in the Qur'an is the root [س-ل-م], which gives birth to various derivations. The word سلم is often interpreted in a limited way as